2020
DOI: 10.3390/nano10122520
|View full text |Cite
|
Sign up to set email alerts
|

Direct and Label-Free Monitoring of Albumin in 2D Fatty Liver Disease Model Using Plasmonic Nanogratings

Abstract: Non-alcoholic fatty liver (NAFLD) is a metabolic disorder related to a chronic lipid accumulation within the hepatocytes. This disease is the most common liver disorder worldwide, and it is estimated that it is present in up to 25% of the world’s population. However, the real prevalence of this disease and the associated disorders is unknown mainly because reliable and applicable diagnostic tools are lacking. It is known that the level of albumin, a pleiotropic protein synthesized by hepatocytes, is correlated… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
3
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
5
3

Relationship

3
5

Authors

Journals

citations
Cited by 8 publications
(4 citation statements)
references
References 20 publications
1
3
0
Order By: Relevance
“…These results demonstrate the detrimental effects of the HS rich in ammonia, ALT, AST and free-DNA on the phenotype and functionality of myotubes. In a previous study (17), we observed the increased albumin release from the hepatocytes upon challenge with NEFAs at 48 h while it dramatically decreases at 72 h of treatment (Figure 4E). This temporary response of the cells suggests that albumin might neutralize, somehow, part of the extracellular lipids.…”
Section: D Fatty Hepatocytes' Supernatant Affects Metabolic Activity ...supporting
confidence: 56%
See 1 more Smart Citation
“…These results demonstrate the detrimental effects of the HS rich in ammonia, ALT, AST and free-DNA on the phenotype and functionality of myotubes. In a previous study (17), we observed the increased albumin release from the hepatocytes upon challenge with NEFAs at 48 h while it dramatically decreases at 72 h of treatment (Figure 4E). This temporary response of the cells suggests that albumin might neutralize, somehow, part of the extracellular lipids.…”
Section: D Fatty Hepatocytes' Supernatant Affects Metabolic Activity ...supporting
confidence: 56%
“…HSA is synthesized exclusively by hepatocytes and released into the bloodstream, where it acts as a transporter of fatty acids. In a previous work, we have demonstrated that hepatocytes cultured in vitro release albumin in response to a lipid challenge for 48 h [17]. The hypothesis is that the increased albumin might be the biological compensation of the hepatocytes to the massive presence of extracellular lipids.…”
Section: Introductionmentioning
confidence: 94%
“…Recently, some works have been published in which OOCs have been integrated with plasmonic biosensors. This technology has been successfully applied to liver ( Lopez-Muñoz et al, 2020 ), muscle ( Lopez-Munõz et al, 2021 ) and pancreas ( Ortega et al, 2021 ) engineered tissue. Although the working range of these sensors is very wide, and saturation effects are not expected, longitudinal monitoring has not yet been tested to date.…”
Section: Integrating Monitoring Tools In Oocsmentioning
confidence: 99%
“…have appeared in the market, a significant number of applications of this principle have been reported during the last years. Recently, localized surface plasmon resonance (LSPR) has been confirmed as a perfect candidate for OOC integration [ 72 ].…”
Section: Organ-on-a-chip 20mentioning
confidence: 99%